2012
DOI: 10.1021/ic202297h
|View full text |Cite
|
Sign up to set email alerts
|

Bright Blue Phosphorescence from Cationic Bis-Cyclometalated Iridium(III) Isocyanide Complexes

Abstract: We report new bis-cyclometalated cationic iridium(III) complexes [(C(^)N)(2)Ir(CN-tert-Bu)(2)](CF(3)SO(3)) that have tert-butyl isocyanides as neutral auxiliary ligands and 2-phenylpyridine or 2-(4'-fluorophenyl)-R-pyridines (where R is 4-methoxy, 4-tert-butyl, or5-trifluoromethyl) as C(^)N ligands. The complexes are white or pale yellow solids that show irreversible reduction and oxidation processes and have a large electrochemical gap of 3.58-3.83 V. They emit blue or blue-green phosphorescence in liquid/sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
135
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 73 publications
(152 citation statements)
references
References 73 publications
14
135
0
3
Order By: Relevance
“…If this is the case, as expected from the larger electronegativity of the N atom, the new LUMO is mainly located on the heterocyclic moiety of the (C^N) ligand (e.g., the pyridine ring for ppy-based ligands). In this way, the use of ancillary ligands with relatively inaccessible p* orbitals (e.g., carbenes [85] or isocyanides [92,93] ) leads to low-lying emitting excited states centered on the cyclometalated ligands and the emitting T 1 state exhibits a more ligand-centered character. In such cases, highly structured emissions and strongly increased radiative lifetimes (i.e., small values of k r ) are found.…”
Section: Molecular-orbital Features Of Ir-itmcsmentioning
confidence: 99%
See 2 more Smart Citations
“…If this is the case, as expected from the larger electronegativity of the N atom, the new LUMO is mainly located on the heterocyclic moiety of the (C^N) ligand (e.g., the pyridine ring for ppy-based ligands). In this way, the use of ancillary ligands with relatively inaccessible p* orbitals (e.g., carbenes [85] or isocyanides [92,93] ) leads to low-lying emitting excited states centered on the cyclometalated ligands and the emitting T 1 state exhibits a more ligand-centered character. In such cases, highly structured emissions and strongly increased radiative lifetimes (i.e., small values of k r ) are found.…”
Section: Molecular-orbital Features Of Ir-itmcsmentioning
confidence: 99%
“…The first two examples of this class of complexes were reported by Thompson et Figure 19) has turned out to be first example of an Ir III isocyanide complex whose strong blue phosphorescence is unaffected by passing from solution to the solid state, thanks to the presence of the tertbutyl groups on the ppy ligand that are particularly effective in preventing self-aggregation. [93] In 2007, Chin et al [120] synthesized a series of cationic iridium complexes equipped with even stronger-field ligands, such as CO. Complexes [Ir(ppy) 2 Figure 19) emit at 451-482 nm and 441-443 nm, respectively. Following an analogous approach, Yang et al [85] have recently reported the first LECs based on N-heterocyclic carbene ligands displaying the bluest emission ever reported for a LEC device (456-488 nm).…”
Section: Ir-itmcs Based On Strong-field Ancillary Ligandsmentioning
confidence: 99%
See 1 more Smart Citation
“…[91] das HOMO aus Ir-dp-Orbitalen (t 2g ) und Phenyl-p-Orbitalen der cyclometallierten C^N-Liganden zusammen, während das LUMO normalerweise am neutralen N^N-Ergänzungsligand lokalisiert ist (Abbildung 16 a). [37] [85] oder Isocyanide [92,93] ) zu tiefer liegenden angeregten Zuständen, die an den cyclometallierten Liganden zentriert sind, und zu einem stärker ligandzentrierten emittierenden T 1 -Zustand. In diesen Fällen beobachtet man stark strukturierte Emissionsbanden und verlängerte Emissionslebensdauern (gleichbedeutend mit kleinen k r -Werten).…”
Section: Spektroskopische Eigenschaften Von Ir-itmcsunclassified
“…This cyclometalated complex of iridium(III) was chosen due to its high stability in aqueous environments present in a living cell (24). In addition, iridium complexes are high yielding phosphorescent compounds that can be rationally tuned to emit visible light across a range of wavelengths (25). At face value, the size of the iridium complex attached to the deoxyribose moiety appears to be very large and would prohibit its utilization as a substrate for any nucleoside transporter.…”
mentioning
confidence: 99%